Hot fuzz - Bevan, Tim.; Park, Nira.; Wright, Edgar, 1974-; Pegg, Simon, 1970-; Freeman, Martin, 1971-; Nighy, Bill, 1949-; Popper, Robert; Cornish, Joe.; Waitt, Chris; Mason, Eric.; Whitelaw, Billie, 1932-; Frost, Nick, 1970-; et al. (Universal City, Calif. : Universal Studios Home Entertainment, 2007)
Nicholas Angel is the finest cop London has to offer. He has an arrest record that is higher than any other officer on the force. As a result, Angel's superiors send him to a place where his talents won't be quite so obvious. They send him to the sleepy and seemingly crime-free village of Sandford. He is partnered with the well-meaning but overeager police officer Danny Butterman, who is the son of the police chief. Danny is a huge action movie fan and believes this may be his chance to experience the life of gunfights and car chases. However, as a series of grisly accidents rocks the village, Angel is convinced that Sandford is not what it seems and as the intrigue deepens, Danny's dreams of explosive, high-octane, car-chasing, gunfighting, all-out action seem more and more like a reality.
Title from container.
Director of photography, Jess Hall ; editor, Chris Dickens ; music, David Arnold ; costume designer, Annie Hardinge ; production designer, Marcus Rowland.
Simon Pegg, Martin Freeman, Bill Nighy, Robert Popper, Joe Cornish, Chris Waitt, Eric Mason, Billie Whitelaw, Nick Frost, Peter Wight, Julia Deakin.
MPAA rating: R; violent content including some graphic images, and language.
DVD
English, dubbed French or dubbed Spanish dialogue, French or Spanish subtitles; English subtitles for the deaf and hard of hearing.
Keywords: Police -- England -- Drama; Accident investigation -- England -- Drama; Police chiefs -- England -- Drama; Criminal behavior -- England -- Drama; Polica̕ -- Inglaterra -- Teatro; Accidentes -- Inglaterra -- Teatro; England -- Drama; Detective and mystery films; Action and adventure films; Comedy films